МЕДИЧНЕ ЦИТУВАННЯ: ПУТІВНИК NLM ДЛЯ АВТОРІВ, РЕДАКТОРІВ І ВИДАВЦІВ - of journal "Morphologia", Editorial office (Морфологія / Morphologia / Morfologìâ, 2021)
К. Петріас (автор), Д. Вендлінг (редактор) Джерело: Patrias K, author; Wendling D, editor. Citing Medicine: The NLM Style Guide for Authors, Editors, and Publishers [Internet]. 2nd edition. Bethesda (MD): National Library of Medicine (US); 2007-. Bookshelf ID: NBK7282 Available from: http://www.ncbi.nlm.nih.gov/books/NBK7256